Rhodamine B removal from aqueous solution by CT269DR resin: Static and dynamic study - Jinbei Yang; Shuyue Yu; Wentao Chen; Yibing Chen (Adsorption Science & Technology)
The adsorption of Rhodamine B onto CT269DR resin has been studied through static and dynamic experiments. The effects of shaking speed, resin dosage, and pH on adsorption were investigated by static experiments. The external mass transfer rate remains substantially unchanged when the shaking speed exceeds 160 r min −1 . The optimal pH range is 5–8, and an increase of resin dosage can directly improve the percentage of removal of Rhodamine B. The equilibrium isotherm data of Rhodamine B on CT269DR resin fit the Langmuir adsorption isotherm well. The thermodynamics parameters, Δ H  = 69.93 kJ mol −1 , Δ S  = 326.73 J mol −1  K −1 , and Δ G  < 0, demonstrate that the adsorption of Rhodamine B onto CT269DR resin is spontaneous and endothermic. The pseudo first-order kinetic model can be successfully used to represent the adsorption process and the activation energy is 25.7 kJ mol −1 . The dynamic experiments show that the breakthrough point is advanced when the flow rate increases and the bed adsorption capacity increases with increasing temperature. Furthermore, the desorption using the solution of 2% NaOH is suitable for desorption and reusing process, and scanning electron microscope (SEM) and fourier transform infrared spectroscopy (FT-IR) analysis reveals that used resin has good wear resistance and chemical stability. The results confirm that CT269DR resin can be employed as an efficient adsorbent for the removal of Rhodamine B from wastewater.